Ancient DNA from Early to Mid-Holocene Burials in Northwestern Argentina: Implications for Understanding the Colonization and Early Populations of South America - Bolnick, Deborah (2014)
Archaeological evidence demonstrates that humans have been living in South America since the late Pleistocene. However, relatively little is known about the genetic diversity present in early hunter-gatherer populations on this continent, and few studies have examined ancient DNA from Pleistocene or early to mid-Holocene human remains from South America. Many questions therefore remain about the early populations of this continent and the routes of migration that were used by some of the earliest settlers.      In this study, we extracted DNA from the remains of 13 individuals unearthed at early and mid-Holocene archaeological sites in northwestern Argentina. The remains come from four locations in the Antofagasta de la Sierra region, in the southern Argentine Puna, and they date between ca. 9500-3330 cal BP. We identified mitochondrial DNA (mtDNA) haplogroups based on coding-region SNPs, and sequenced 372 base pairs of the first hypervariable region of the mtDNA to confirm haplogroup assignments and define mtDNA haplotypes. All results were confirmed through multiple independent DNA extractions and PCR amplifications. We compared the genetic lineages in these individuals with those in other ancient and contemporary populations from the Americas to help elucidate the genetic affinities between the prehistoric inhabitants of the Puna and peoples in other regions. We found that one of the most common mtDNA lineages in these ancient Argentines was haplogroup D4h3a, which is rare in indigenous Americans today but most common along the Pacific coast. Our results shed light on the early populations and routes of migration in South America.